Determination of some heavy metals in honey - FüsunTemamoğulları Md. Motahar Hussain FüsunTemamoğulları; Selma Yazar; Ruhtan Başkaya (Eurasian Journal of Veterinary Sciences)
Aim: To determine some heavy metal content in honey samples collected from twenty different villages around Ataturk Dam in Sanliurfa. Materials and Methods: Heavy metal content was determined from hundred natural liquid honey samples with graphite furnace atomic absorption spectrometer. Results: Lead and Cadmium levels were determined as 0.349±0.147 (0.000-0.642) and 0.003±0.007 (0.000-0.038) ppm, respectively, Manganese was not detected in honey samples. From the point of lead and cadmium contents, the differences between villages were not found statistically significant (p>0.05). Conclusion: When the consumption of the honey produced in Şanlıurfa is considered, it can be stated that they are harmless from the point of heavy metal content